Improvement and quality evaluation of rutab date paste fortified with wheat germ - A. S. Dyab; Kh. M. Atieya; M. A. Abdel Salam (Пищевые системы, 2025)
This investigation aimed to utilize wheat germ to improve the nutritional value and sensory properties of date pastes. Wheat germ was added to the soft date paste at different concentrations (5, 10%, and 15%). Chemical composition, bioactive compounds, browning index, fatty acids, microbiological quality, and peroxide values were estimated. Substitution with wheat germ significantly increased the ash, protein, and fat contents of the treatments, and decreased total sugars and total carbohydrates. In addition, the incorporation of wheat germ into the date paste led to a decrease in water activity. The color index of fortified date paste was improved and unsaturated fatty acids, such as oleic acid, linoleic acid, and linolenic acid, increased. A reduction in the total bacterial, yeast, and mold counts was observed. The highest score of the index of acceptance was recorded for 15%, followed by 10% and 5%, and the lowest score was for the control sample.